2022
DOI: 10.3389/fmedt.2022.980735
|View full text |Cite
|
Sign up to set email alerts
|

Medical decision support system using weakly-labeled lung CT scans

Abstract: PurposeDetermination and development of an effective set of models leveraging Artificial Intelligence techniques to generate a system able to support clinical practitioners working with COVID-19 patients. It involves a pipeline including classification, lung and lesion segmentation, as well as lesion quantification of axial lung CT studies.ApproachA deep neural network architecture based on DenseNet is introduced for the classification of weakly-labeled, variable-sized (and possibly sparse) axial lung CT scans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…ML was the most frequently used method to develop CDSS for COVID‐19 diagnosis. The most common ML methods in the reviewed studies were CNN 34–85 . In line with this result, other review studies also indicated CNN to be the most common method to develop a system for COVID‐19 diagnosis 23,25,27,28,30,100 .…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…ML was the most frequently used method to develop CDSS for COVID‐19 diagnosis. The most common ML methods in the reviewed studies were CNN 34–85 . In line with this result, other review studies also indicated CNN to be the most common method to develop a system for COVID‐19 diagnosis 23,25,27,28,30,100 .…”
Section: Discussionsupporting
confidence: 54%
“…These studies also recommended the use of CDSS in future research. Finally, 68 articles met all the inclusion criteria 5,17,34–99 . The flowchart of the selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations